Issues of infrastructural development: a synthesis of the literature - Ahmed, Raisuddin; Donovan, Cynthia (International Food Policy Research Institute, 1992)
Economists have long been working to discover why some countries move ahead fast, while others lag behind on the path of economic development. The role of infrastructural factors in economic development either remains to be fully unfolded or has been unraveled with a considerable degree of ambiguity. The objective of this paper is to scan the literature on infrastructure in order to establish the state of knowledge on the subject.